Lumbar and pelvis movement comparison between cross-court and long-line topspin forehand in table tennis: based on musculoskeletal model - He, Yuqi; Liang, Minjun; Fang, Yufei; Fekete, Gusztáv; Baker, Julien S.; Gu, Yaodong (Frontiers in Bioengineering and Biotechnology, 2023)
Cross-court and the long-line topspin forehand is the common and basic stroke skill in table tennis. The purpose of this study was to investigate the differences in lumbar and pelvis movements between cross-court and long-line topspin forehand strokes in table tennis based on musculoskeletal demands using OpenSim. The eight-camera Vicon system and Kistler force platform were used to measure kinematics and kinetics in the lumbar and pelvis movement of sixteen participants (Weight: 69.89±1.58 kg; Height: 1.73±0.03 m; Age: 22.89±2.03 years; BMI: 23.45±0.69 kg/m2; Experience: 8.33±0.71 years) during cross-court and long-line topspin forehand play. The data was imputed into OpenSim providing the establishment of the Giat2392 musculoskeletal model for simulation. One-dimensional statistical parametric mapping and independent samples t-test was performed in MATLAB and SPSS to analyze the kinematics and kinetics. The results show that the range of motion, peak moment, and maximum angle of the lumbar and pelvis movement in cross-court play were significantly higher than in the long-line. The moment of long-line in the sagittal and frontal plane was significantly higher than cross-court play in the early stroke phase. The lumbar and pelvis embody greater weight transfer and greater energy production mechanisms when players performed cross-court compared to long-line topspin forehand. It is important to note that players are also at greater risk of lumbar injury in cross-court play. Beginners could enhance their motor control strategies in forehand topspin skills and master this skill more easily based on the results of this study.